Annual Plan 1995-96 Volume-III V. Energy; VI, Industry and Minerals General Areas Government of Assam - Planning Commission (Planning Commission, 1995)
The investment in the Power Sector was not encouraging during the first two years of the 8th Five Year Plan. the allocation during these years were reduced considerably due to resource crutch. The plan releases during the year 1994-95 has been till December 94. This has adversely affected implementation of Plan programme during, the current year.
Government of Assam, Planning and Development Department